Global tuberculosis report 2018 - Anderson, Laura (World Health Organization, 2018)
This edition is published in the lead up to the UN high-level meeting on TB. It provides a comprehensive and up-to-date assessment of the TB epidemic, and of progress in the response to the epidemic, at global, regional and country levels. The report is bases primarily on data reported annually to WHO by countries, and databases maintained by other UN agencies and the World Bank